ANALYSIS OF THE ORGANIZATIONAL GOVERNANCE OF REGIONAL GOVERNMENT AGENCIES IN ROAD CLEANLINESS MANAGEMENT AT THE ENVIRONMENTAL SERVICE OFFICE OF MADIUN CITY: Analisis Tata Kelola Organisasi Perangkat Daerah Dalam Pengelolaan Kebersihan Jalan di Dinas Lingkungan Hidup Kota Madiun - DAFFA FADHILA; Agus Santoso; Harianto; Agus Wiyaka (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the governance of regional government organizations in street cleanliness management implemented by the Madiun City Environmental Agency. This study uses a qualitative approach with a descriptive approach. Informants in this study include several parties directly involved in the implementation of street cleanliness management, including the Head of the Madiun City Environmental Agency, the Head of the Sanitation or Waste Division, street cleaners, and eight community members living in the area where the street cleanliness is managed. Data collection techniques used documentation and interviews. Data analysis in this study employed qualitative descriptive analysis. The research results indicate that street cleanliness management in Madiun City has been running quite well, but still requires improvement, particularly in terms of community participation and equitable program implementation